2020
DOI: 10.21203/rs.3.rs-32388/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccination concerns, beliefs and practices among Ukrainian migrants in Poland: A qualitative study

Abstract: Objectives Ukrainians numbering approximately 1.2 million are the largest migrant group in Poland. Data on vaccination coverage among migrants are not collected in EU, including Poland. Therefore, this qualitative study aimed to identify vaccination practices in this migrant group, to explore facilitators and barriers to vaccination and related access to Polish healthcare services. Methods In September 2019, a qualitative study of Ukrainian migrants (UMs) living in Szczecin, Poland, and recruited through a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…After title, abstract and full-text screening, 63 papers were identified and included in this review, see for vaccine refusal (45). Risk perception has been shown to be important among migrant communities when making vaccination decisions (46), with the perceived dangers of vaccination weighed against complacency around either the need for vaccination (47) or perceptions of danger relating to the specific vaccine-preventable disease (48). In some communities, preferences exist for 'more natural' options such as herbal remedies, avoiding human contact, reliance on our immune system (40,44).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After title, abstract and full-text screening, 63 papers were identified and included in this review, see for vaccine refusal (45). Risk perception has been shown to be important among migrant communities when making vaccination decisions (46), with the perceived dangers of vaccination weighed against complacency around either the need for vaccination (47) or perceptions of danger relating to the specific vaccine-preventable disease (48). In some communities, preferences exist for 'more natural' options such as herbal remedies, avoiding human contact, reliance on our immune system (40,44).…”
Section: Resultsmentioning
confidence: 99%
“…Several papers suggest that economic barriers and affordability of vaccines are also important in decision making for some refugees and migrants (40,47,52,53,57,62,64,67,94). This can include direct costs; for example, Louka et al found that asylum seekers in Greece and the Netherlands became less likely to accept vaccination as the cost increased (57).…”
Section: Social Processes: Drivers or Inhibitors Of Individual Motiva...mentioning
confidence: 99%
See 3 more Smart Citations